Instantaneous and Compound Growth Analysis for the Consumption and Production of Rice and its Implication for Empowement Program in Nigeria - Zakari , Justine; Abakpa, Augustine; Oranu, Richard; Vandu, Jonathan M.; Babangida, Adams (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2020)
This study was necessitated as a result of the existing yield gap between rice production and consumption in Nigeria. This research aimed to determine the instantaneous and compound growth rates of rice consumption and production in Nigeria over the period of 1994 to 2019 and its empowerment impact. Time series data on the aggregate rice consumption and production obtained from the database of United State Department for Agriculture (USDA) foreign agricultural service were employed in this study. A semi-log growth rate model was employed to analyze the time series data using E-views 8.5 and the result of the analysis showed that the instantaneous and compound growth rates(5% and 5.13%) of rice consumption were higher than that of rice production (4.5% and 4.6%) and this indicates that the incidence of consumption-production gap for rice in Nigeria has been an existing trend over the years and the trend would continue if appropriate measures are not put in place. The implication of this finding is that the untapped potentials of Nigeria for rice production should be exploited for the empowerment of Nigerian youths in the area of rice production and women in the area of rice processing. This research work hereby recommends that government should provide comprehensive farmer education and technical assistant, continued engagement between the federal government and the states governments and the provision of value-chain training to rice farmers in Nigeria.